THE CASELAW OF THE CONSTITUTIONAL COURT REGARDING THE CONSTITUTIONALITY OF THE PARLIAMENTARY ELECTORAL SYSTEM OF HUNGARY BETWEEN 2012 AND 2017 - Téglási, András (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
By adopting the new Constitution of Hungary in the year 2011 (Fundamental Law), the Parliament also reformed the rules governing the election of members of parliament. The first important step of electoral legislation is the Act CCIII of 2011 on the election of members of parliament, and then the Act XXXVI of 2013 on Electoral Procedure was also adopted by the Hungarian Parliament. The material and procedural rules for the elections have introduced many novelties that have been criticized for many, including constitutional considerations. The Constitutional Court of Hungary has been examining the electoral rules since the beginning, right from the moment of adoption of the act on electoral procedures (Ve.). This paper introduces systematically the Constitutional Court’s decisions on legal norms for parliamentary elections.